Comparison of biomechanical characteristics of the Schneiderian membrane with different transcrestal sinus floor elevation techniques using three-dimensional finite element analysis - Xi Lin; Siqi Xu; Lijuan Chen; Guoying Que (BMC Oral Health)
Abstract Objective The aim of this study was to establish a three-dimensional finite element (FE) hydraulic pressure technique model and compare the biomechanical characteristics of the osteotome technique and the hydraulic pressure technique using three-dimensional finite element analysis (FEA). Methods Three FE models were created: the hydraulic pressure technique (M1), the osteotome technique with a Ø 1.6-mm osteotome (M2), and the osteotome technique with a Ø 3.0-mm osteotome (M3) models. Three models were simulated via computer-aided design software, with the sinus membrane elevated to 1, 3 and 5 mm, after which the required loading force was recorded. Stress distribution, including the equivalent von Mises stress, tensile stress, compressive stress, shear stress, as well as strain (i.e., sinus membrane displacement in horizontal dimensions) of the three models were subsequently examined and statistically compared. Results Overall, the required loading force, stress and strain increased as the elevation height increased. The loading force required to elevate the sinus membrane to 1,3 and 5 mm in M1 was 24.9 kPa, 77.1 kPa and 130 kPa, comparing 32.5 kPa, 112. 9 kPa and 200.8 kPa in M2 as well as 54.5 kPa, 160.6 kPa and 273.2 kPa in M3. Under the same elevation height, M1 exhibited the least von Mises stress (P<0.001), as well as the largest horizontal sinus membrane displacement (P<0.001). Conclusions It can be seen from the FEA results that the hydraulic pressure technique enables a greater portion of the sinus membrane to detach from the sinus floor while exerting less stress on the mucosa when the sinus membrane is elevated up to 5 mm. Based on this study, the hydraulic pressure technique was found to be safer and more effective than the osteotome technique under the same elevation height.